Effectiveness Of Local Probiotic Enzyme Fermented Feeddigestion On The Production And Quality Of Eggs From Local Hybrid Chickens In The Laying Phase - Alkausar; Muhammad Aman Yaman; Wenny Ladhunka Nur Aliyya; Riski Ambia Rahman (Jurnal Ternak, 2025)
Improving the egg productivity and quality of local hybrid chicken is an important strategy in the development of sustainable poultry farming in Indonesia. This study aims to evaluate the effectiveness of fermented diet enriched with local probiotics and digestive enzymes on egg production and quality of local hybrid chicken during the laying phase. The study was conducted at the Field Laboratory of Animal Husbandry, Syiah Kuala University and the Laboratory of Animal Physiology and Reproduction Teuku Umar University, using 120 chickens resulting from the crossbreeding of female ALPU and male KUB F2. The research design used a completely randomised method with 4 treatments and 5 replicates: P0 (100% commercial diet), P1 (100% fermented diet), P2 (50% fermented diet + 50% commercial diet), and P3 (30% fermented diet + 70% commercial diet). The results showed that treatment P1 had a significant effect (P<0.05) on egg production, egg weight, and egg yolk colour score. However, no significant differences were observed in clutch size, shell thickness, and egg grade. The effectiveness of fermented diet is thought to stem from improved digestibility and nutrients absorption due to the presence of probiotics and digestive enzymes. Treatments P2 and P3 showed that the result was equivalent to that of on commercial diet. Overall, fermented diet enriched with probiotic and digestive enzymes proved to be an effective to stimulate egg production and quality on local hybrid laying chickens. In addition, this findings could be an economical alternative for improving the production and quality of eggs from local hybrid chickens in the early laying phase